A multiprimary lighting system for customized color stimuli. Issue 1 (1st June 2021) - Yuan, Yue; Murdoch, Michael J.; Fairchild, Mark D.
Abstract: In this article, a dual seven‐primary lighting system is constructed for color research and education. The system offers sufficient spectral variability to approximate the spectral power distribution of a variety of standard illuminants. More importantly, the constructed multiprimary lighting system was verified to have crucial advantages over conventional displays/projectors to probe observer metamerism through the generation of individualized metameric color stimuli. An observer metamerism index to describe the potential for observer metamerism of any generated stimulus pairs with respect to the population variation of color‐normal observers is formulated. The metric is further extended for use in quantifying the potential for observer metamerism of any lighting system or a system‐primary combination. Moreover, 10 pairs of lighting stimuli, customized for exhibiting high degrees of observer variability, were produced using the system as a step toward creating a device for the color matching functions characterization of individual observers, a so‐called observer calibrator.